First record of Macrocheles caelatus Berlese (Mesostigmata, Macrochelidae) from Iran - Fateme Saeed; Shahrooz Kazemi (Persian Journal of Acarology)
In a faunistic survey on edaphic Mesostigmata in some parks in Kerman City, a female specimen of M. caelatus Berlese, 1918 was collected which considered as a new record for Iran mite fauna.